Effects of Electron-Beam Pretreatment on Anodically Grown TiO2 Nanotubes. (1st January 2015) - Choi, Yong-Wook; Seong, Mijeong; Yoo, Hyeonseok; Park, Dong-Wha; Oh, Seung Kyu; Kwak, Joon Seop; Jung, Yongan; Choi, Jinsub
Abstract : A Ti substrate was pretreated with an electron beam (E-beam) at RF 150 W and DC 1500 V for 1 h under Ar atmosphere and then anodized in a 1 M H3 PO4 /1 M NaOH/0.5 wt% HF solution at 20 V. The E-beam pretreatment led to a change in the composition surface, resulting in delayed nucleation of the nanotubes at the beginning of the anodization but a thicker oxide formation at the end of anodization because of the initial formation of a protective oxide that prevents the dissolution of the formed nanotubes in the electrolyte.